Environmental determinants of larval herring (Clupea harengus) abundance and distribution in the western Baltic Sea. (27th September 2018) - Dodson, J. J.; Daigle, G.; Hammer, C.; Polte, P.; Kotterba, P.; Winkler, G.; Zimmermann, C.
Abstract: The analysis of the abundance and distribution of the early life‐history stages of the western Baltic spring‐spawning herring population, spanning 23 yr, revealed that the abundance of yolk‐sac larvae was strongly spatially structured and significantly more abundant during the optimal temperature window for viable hatch of herring larvae (9°C to 13°C). The percentage of time encompassing this optimal temperature window exhibited a major contraction between 1995 and 2000 that may have contributed to reducing the supply of yolk‐sac larvae and ultimately contributed to reducing recruitment observed after 2000. Temperature also significantly influenced the abundance of preflexion and flexion larvae, defining dome‐shaped responses with maximum abundances observed between 10.27°C and 13.43°C and between 13.68°C and 18.53°C, respectively. The abundances of postflexion stage larvae were greatest at temperatures exceeding 14°C with no apparent decline in abundance at temperatures of up to 20°C. Temperature also played a significant role in influencing the abundance of larvae through its interaction with the abundance of the preceding developmental stage and provided evidence of stage‐specific temperature‐related mortality. There was also evidence of reduced survival during the preflexion–flexion transition in cohorts produced early in the season relative to those cohorts produced later. Although phenologically plastic species such as herring may be able to alter the dates of spawning, thus partially mitigating the effects of increasing rates of spring warming, constriction of the temperature windows for successful hatching and subsequent ontogenetic development may not be so easily mitigated by changes in phenology.